Impact on Social Inclusion Processes of Children with Visual Impairments at CRAC Through the Teaching of Skating (ACTIVIDAD FÍSICA Y DESARROLLO HUMANO, 2022)
In recent years, social inclusion has gained significant attention through the creation of spaces for participation, interaction, and integration, responding to individual differences. These spaces are fundamental factors in both personal development (including social, emotional, physical, and cognitive dimensions) and collective development, fostering all types of social relationships among diverse groups.Children with visual impairments, aged 6 to 12, from the Rehabilitation Center for Blind Adults (CRAC), are the main participants in this study, which used a non-probabilistic sampling method. This research project aims to recognize the impact of teaching skating on the social inclusion processes of children with visual impairments at CRAC, focusing on the principles derived from this sport, such as axiological formation (self-concept) and functional development (skills acquisition).The study adopts a qualitative approach, seeking to understand the community environment by exploring the description and interpretation of its social practices. Additionally, a socio-critical paradigm is applied, which allows for guiding the socialization of realities, experiences, and subjective meanings from a social perspective.As a result, the research led to the creation of new inclusive educational strategies focused on axiological development and collective awareness for the use and adaptation of recreational-sport spaces in skating practice for children with visual impairments, in collaboration with other social actors. It also contributed to adapting intervention methodologies, thereby promoting the participants’ development and active participation in society.